2020
DOI: 10.1111/avj.13005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of Australian livestock producers concerning biosecurity practices

Abstract: Biosecurity risks are a major threat to the profitability of the industry as well as impacting human and animal health. Livestock producers play a crucial role in biosecurity as the first to notice changes in the health or productivity of their stock and are generally responsible for implementing protective measures. However, uptake of biosecurity measures by producers is variable. We critically appraised the current literature regarding biosecurity practices in Australian livestock industries and highlight as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…As a result, there is a noticeable transition occurring from traditional small-scale production to large-scale commercial production to meet these increasing demands [9]. Previous research has indicated that medium and large farmers are more aware and interested in adopting biosecurity interventions [29,30]. This explains the voluntary participation of the majority of the medium and large-scale dairy farmers in the study region.…”
Section: Discussionmentioning
confidence: 89%
“…As a result, there is a noticeable transition occurring from traditional small-scale production to large-scale commercial production to meet these increasing demands [9]. Previous research has indicated that medium and large farmers are more aware and interested in adopting biosecurity interventions [29,30]. This explains the voluntary participation of the majority of the medium and large-scale dairy farmers in the study region.…”
Section: Discussionmentioning
confidence: 89%
“…Some government veterinary services highlighted a lack of biosecurity awareness among farmers, which could be the fault of government veterinarians, or of private veterinarians, to whom farmers often turn to for reliable information ( 63 ). Hence it could be interesting to evaluate the impact of the sanctioning and advisory roles served mainly by the government veterinary services, but also by private veterinarians, regarding the ultimate day-to-day implementation of biosecurity measures by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that animal viruses are classified into six groups and, depending on the structure, type of viral genome and size, differ in their resistance to disinfectants (Paquette et al, 2020;Tarka & Nitsch-Osuch, 2021).…”
Section: Introductionmentioning
confidence: 99%